The Performance of Sharia Equity Fund Investment Manager - Maftukhah, Anni (Jurnal Iqtisaduna, 2020)
Sharia mutual funds are fund raising activities from investors to be managed by investment managers with sharia-based management, namely by not investing funds in companies whose types and scope of business are not in accordance with Islamic sharia. This study was conducted to determine the effect of turnover ratio, expenses ratio, fund size, managerial tenure, and fund selection skills on the performance of sharia mutual fund investment managers in Indonesia. The data used in this study are monthly Net Asset Value, BI rate, IHSG, annual turnover data, annual expenses ratio data, and prospectus of 9 sharia stock mutual funds from December 2014 to December 2018. Samples were taken based on the purposive sampling method during this research. The measurement of the performance of sharia equity fund investment managers uses the Sharpe Ratio method. The method used is multiple linear regression analysis and classic assumption tests using descriptive statistical tests, multicollinearity tests, and heteroscedasticity tests using EVIEWS 10 statistical software. The results of this study indicate that turnover ratio, fund size, fund selection skills significantly influence performance Islamic mutual fund investment manager. While expenses and managerial tenure ratios do not significantly influence the performance of investment managers in Islamic mutual funds.